Factors affecting the performance of cooperative societies in Bahrain, case study of three consumer cooperative societies - Al Mahmood, Ahmed Abdulrazaq Mohammed (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2014)
This study gives a general introduction of cooperative societies and their importance in the economic development for countries. The study focused on Bahrain and the performance of cooperative societies since the establishment of the Cooperative Act in 1972. The main problem of this study is that the cooperative societies are not being supported in Bahrain by the govermnent and will not be able to survive in the open market. Thus, this will reduce the people desire to be engaged in the cooperative societies and be a part of it. To achieve the study objectives the researcher used descriptive and analytical approaches. The data used for this study had focused on the secondary data collected from Hidd, Jsa town and Sanabis Consumer Cooperative Societies from 1999 to 2012. Then these data were analyzed in E-view. The results of the analyses show that the net profit for Hidd consumer cooperative society and lsa Town consumer cooperative society is affected by the petrol station sales, while Sanabis consumer cooperative society's net profit is not affected by the petrol station sales. The study also shows that consumer cooperative societies is providing welfare for the members based on his purchasing from the society. Finally, to improve the cooperative societies sector the researcher recommended to develop a strategy to have a secure and sustainable income for the consumer cooperative societies and to do a SWOT analysis. Nevertheless, educating the students in schools and universities can be considered a big support from the govermnent to cooperative sector.